RESOLUTION OF LAND DISPUTES THROUGH CUSTOMARY LAW IN PANAKKUKANG, GOWA REGENCY FROM THE PERSPECTIVE OF SIYASAH SYAR’IYYAH - Tri Buwonot Tungga Dewi (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to examine the settlement of land disputes through customary law in Panakkukang, Gowa Regency, from a siyasah syar'iyyah perspective. This is a qualitative study. The research design is field research. The results of this study show that: First, the practice of settling land disputes through customary law in Panakkukang Village, Gowa Regency. For example, calling the disputing parties to discuss the issue amicably, making consensus deliberation the main value and principle that forms the legal basis for land dispute resolution in Panakkukang Village, Gowa Regency, and the division of land in disputes with the aim of achieving justice. In addition, there is a lack of clarity regarding the role of customary authorities in resolving land disputes through customary law in Panakkukang Village. Second, the practice of resolving land disputes through customary law in Panakkukang Village, Gowa Regency, is not fully in line with Siyasah Syar'iyyah. This is partly due to the absence of clear customary authorities in the settlement of land disputes through customary law in Panakkukang Village. This non-alignment is due to the actions of the government, in this case the village officials, who have not demonstrated any benefits in this stage.